Pelatihan Pembuatan Kitchen Garden di Desa Glagahwero Jember sebagai Upaya Menuju Desa Agroeduwisata : Training on the Production Plant Growth Promoting Rhizobacteria based on Bamboo Root for the Karangrejo-Jember Farmer as an environmental agricultural solution - Wilujeng, Elly Daru Ika; Adnan, Moch. Rosyadi; Rahmawati, Dwi; Ermawati, Netty; Maulinda, Restiana; Prasetyo, Hari (Agrimas : Jurnal Pengabdian Masyarakat Bidang Pertanian, 2025)
Located in Kalisat Subdistrict, Jember Regency, Glagahwero Village has abundant potential, encompassing water rafting adventures, smart green house structures, and the appealing "Beroeng Sorah" eatery. The "Beroeng Sorah" eatery functions as a vital cornerstone to enhance the appeal of water rafting tourism. However, the lack of surrounding greenery contributes to a warmer atmosphere, especially during the summer months. Therefore, a dedicated training and mentoring initiative focused on establishing kitchen gardens was implemented in Glagahwero, strategically located near the "Beroeng Sorah" eatery. This activity aimed to draw tourists to visit Glagahwero. Held on July 27, 2024, at the "Beroeng Sorah" cafe, the program engaged local youth groups and the PKK members. The training employed a combination of informative lectures and interactive discussions, covering topics from the fundamentals and benefits of kitchen gardens, the art of designing kitchen gardens, and the implementation steps. This project has been successfully adopted, implemented, and managed by the youth community of Desa Glagahwero to support water rafting tourism. The people of Glagahwero received the benefits of the kitchen garden practice and acknowledged its positive impact on environmental sustainability. Ultimately, the community looks forward to future programs to further enhance public knowledge and strategically develop the village's potential into a thriving agro-edu-tourism destination